The Personnel Development Towards Digital Transformation Disruption of Personnel in the Excise Department - Butpho, Monsicha; Holumyong, Thitima (Legal State Journal, 2023)
This research article aims (1) to assess the level of technological competency development of personnel in the Excise Department, (2) to compare technological competency development of personnel in the Excise Department, categorized by population characteristics, and (3) to test a correlation between technological competency development and factors affecting technological competency development. The samples of this quantitative research were 250 government officials of the Central Excise Department. Data was collected through questionnaires. Statistical methods to analyze the data were frequency, percentage, mean, standard deviation, t test, One-Way ANOVA, and Pearson’s product moment correlation coefficient. Findings are as follows: (1) the level of technological competency development of personnel in the Excise Department was at a high level, (2) a comparative analysis of technological competency development of personal in the Excise Department, categorized by personal factors was found different, and (3) there was a relatively high positive correlation between the technological competency development of personnel in the Excise Department and the factors affecting the development.